HEART FAILURE AND FIRST DOSE HYPOTENSION AFTER ANGIOTENSIN CONVERTING ENZYME INHIBITORS - Vitovec, Jiri; Spinar, Jindrich (Biomedical papers, 2004)
The first-dose induced decrease in blood pressure in some patients following the administration of ACE inhibitors is a fact causing some concern among clinicians prescribing these drugs. However, an overview of clinical trials and the authors' own experience clearly point to the possibility of reducing the incidence and/or severity of first-dose hypotension. Apart from appropriate clinical measures to be taken, the choice of the ACE inhibitor seems to be of crucial importance as some (fosinopril, perindopril) produce less hypotension than others. Thus, with due circumspection, ACE inhibitors can safely retain their position as the cornerstone of the treatment of chronic heart failure.
Keywords: ACE inhibitors/Heart Failure/Myocardial Infarction/First-Dose Hypotension